Threading time : a cultural history of threadwork - Bausum, Dolores (TCU Press, 2001)
"This is a book about both art and people. The author draws on stories about threadworkers from ancient literature - the Bible, the Iliad, and the Odyssey - and from more recent works by such authors as Nathaniel Hawthorne, Theodore Dreiser, Margaret Mitchell, and John Updike. Works by two Germans - play-wright Gerhart Hauptmann and artist Kathe Kollwitz - and English poets such as Robert Burns and William Blake illustrate the sweatshops characteristic of textile and garment production for centuries, a pattern that persists today in developing countries." "Artistic images from classic sculpture, a window from the Cathedral at Chartres, paintings by such masters as Vermeer and Monet, twentieth-century quilts, and works by contemporary painters such as Elien Day Hale and Margaret Schillie further illustrate the significence of thread-work." "As an original view of threadwork and those who create it written from a broad chronological perspective, Threading Time reaches beyond textile artisans and collectors to present a study significant to readers of literature, women's history, and cultural history."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved